2020
DOI: 10.1002/jbt.22676
|View full text |Cite
|
Sign up to set email alerts
|

The potential toxic effects of magnesium oxide nanoparticles and valproate on liver tissue

Abstract: The liver is the main organ responsible for drug and xenobiotic metabolism and detoxification in the body. There are many antiepileptic drugs and nanoparticles that have been reported to cause serious untoward biological responses and hepatotoxicity. The aim of this study is to investigate the potential toxic effect of aspartic acid‐coated magnesium oxide nanoparticles (Mg nano) and valproate (valp) using an in vitro three‐dimensional (3D) human liver organoid model and an in vivo pentylenetetrazole (PTZ)‐indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In order to investigate the effect of nanomaterials on the liver, a 3D liver model with liver-specific functions must be created in vitro . Several studies have been reported on the effects of nanomaterials on 3D liver models [ 30 , 42 , 43 , 44 , 45 ]. Kermanizadeh A. et al evaluated the hepatotoxicity of human liver cell heterospheroids by various nanomaterials (Ag, ZnO, MWCNT, and a positively charged TiO 2 ) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the effect of nanomaterials on the liver, a 3D liver model with liver-specific functions must be created in vitro . Several studies have been reported on the effects of nanomaterials on 3D liver models [ 30 , 42 , 43 , 44 , 45 ]. Kermanizadeh A. et al evaluated the hepatotoxicity of human liver cell heterospheroids by various nanomaterials (Ag, ZnO, MWCNT, and a positively charged TiO 2 ) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kermanizadeh A. et al evaluated the hepatotoxicity of human liver cell heterospheroids by various nanomaterials (Ag, ZnO, MWCNT, and a positively charged TiO 2 ) [ 42 ]. Mekky G. et al reported on the effects of magnesium oxide nanoparticles using primary human liver cell heterospheroids and animals [ 43 ]. Tee J.K. et al reported on the effects of TiO 2 nanoparticles using LO2 cell–sinusoidal endothelial cell heterospheroids [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human liver organoids were used to test the toxicity of aspartic acid-coated magnesium oxide nanoparticles and valproate. These two drugs have toxic effects on the liver organoids by reducing cell viability, reducing ATP, and increasing reactive oxygen species ( Mekky et al, 2021 ). Liver organoids were applied to verify the toxicity of drugs that had been withdrawn from the market due to hepatotoxicity, such as troglitazone, trovafloxacin.…”
Section: Application Of Organoids In Crc Researchmentioning
confidence: 99%
“…14 Gelli et al (2015) highlighted the pulmonary toxicity that MgO-NPs produced in rats, and Mekky and coworkers (2021) revealed elevated serum alanine aminotransferase and aspartate aminotransferase levels suggesting potential toxic effects of nano Mg on the liver tissue samples of a rat convulsion model. 15,16 In vitro, contradictory results have been reported about the toxicity of MgO-NPs. While some authors described that exposure of various mammalian cell lines to MgO-NPs led to cytotoxic effects, such as reduced cell viability, mitochondrial and lysosomal malfunctions, DNA damage, oxidative stress, and apoptosis, Mittag et al (2019) indicated that MgO-NPs had no cytotoxic or genotoxic effects in intestinal HT29 cells and did not induce apoptosis, cell cycle changes, or oxidative stress.…”
Section: Introductionmentioning
confidence: 99%